2023
DOI: 10.3390/microorganisms11071651
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Feasibility of Employing a Combination of a Bacteriophage-Derived Endolysin and Spore Germinants to Treat Relapsing Clostridioides difficile Infection

Abstract: Clostridioides difficile is a Gram-positive, anaerobic, spore-forming bacillus and is a major cause of healthcare-associated infections. Whereas the vegetative form of the pathogen is susceptible to treatment with antibiotics, its ability to persist in the gut as antibiotic-resistant spores means that reinfection can occur in cases were the individual fails to re-establish a protective microflora. Bacteriophages and their lysins are currently being explored as treatment options due to their specificity, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Hence, combination therapy that includes spore germinants could promote germination, therefore ensuring maximum killing of the infected strain. This strategy has, however, been shown to interfere with endolysin activity, as the massive release of calcium during germination is shown to inhibit the activity of LysCD6356, at least in vitro ( 38 ). The importance of this observation to the in vivo condition requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, combination therapy that includes spore germinants could promote germination, therefore ensuring maximum killing of the infected strain. This strategy has, however, been shown to interfere with endolysin activity, as the massive release of calcium during germination is shown to inhibit the activity of LysCD6356, at least in vitro ( 38 ). The importance of this observation to the in vivo condition requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, one common observation that has been reported with all C. difficile phage endolysins is that the catalytic domain of the enzyme alone (EAD) is sufficient for full activity. In fact, the removal of the CBD was reported to increase the lytic activity of C. difficile ( 30 32 , 36 , 38 ). It was also shown that the CBD from the CD16/50L endolysin was responsible for trapping the endolysin within cellular debris after lysis.…”
Section: Cell Wall-degrading Enzymes As Antimicrobialsmentioning
confidence: 99%
See 1 more Smart Citation